Coffee Plantation Agrotourism Development Strategy with SWOT Analysis in Penggung Village, Pacitan Regency - Jenvia Rista Pratiwi; Rita Parmawati; Luchman Hakim (Indonesian Journal of Environment and Sustainable Development, 2021)
Penggung Village is included in Pacitan Regency, an Agropolitan Area based on the Pacitan Regional Spatial Plan in 2005-2025. Development is carried out in the tourism sector with agriculture as the point. The main commodity is coffee plantations. The development is carried out with the Coffee Plantation Agrotourism concept. It pays attention to the sustainability of the natural environment and can increase the prosperity of the people of Penggung Village. This study aims to analyze the factors that become strengths, weaknesses, opportunities, and threats to developing coffee plantation agro-tourism and can determine the best strategy for achieving success in the development of coffee plantation agro-tourism in Penggung Village, Nawangan District, Pacitan Regency. The method used is a mixed (quantitative and qualitative) SWOT analysis by evaluating strengths and weaknesses as internal factors (IFE), while opportunities and threats as external factors (EFE). The results showed the development of Coffee Plantation Agrotourism in Penggung Village Pacitan Regency is still not optimal in the provision of tourism facilities and infrastructure, as the cultivation technology used is also not optimal. The strategy that can be used is diversification in the fourth quadrant, which gives rise to four strategies. This study suggests researching the quality of liberica coffee species, the leading commodities in Penggung Village, for the sustainability of Coffee Plantation Agrotourism in Penggung Village, Pacitan Regency. Keyword : agrotourism, coffee plantation, SWOT analysis